Taichi qi flow in the kinematic process of piano playing: an application of Chinese science - Loo, Fung Ying; Loo, Fung Chiat (IDOSI Publications, 2013)
Reviewing different views and definitions labelling the psychological state of ‘being’ when a musician reaches peak performance, this study examines the hypothetical assumption that theories and movement from taichi’s qi flow (the Chinese medical term for vital force) may be a factor in contributing to what various scholars in psychological study as ‘flow,’ ‘peak experience,’ ‘heightened arousal,’ ‘becoming’ and so forth. The phenomenon and existence of the Chinese traditional scientific belief in qi flow is examined and applied to piano playing. Whether qi is just an experience similar to blood circulation in a Western viewpoint is considered. As a result of taichi motion analysis and practice-led research, three major factors contributing to qi flow are identified. The concept of yin and yang in taichi together with circular motion and the attainment of qi flow are highlighted. The article exemplifies a new mind-body concept from a taichi perspective and its application to the kinematic process of piano playing.